Needs Analysis of Technology Applications for Differentiated Learning on Geometry Materials in Semarang City Elementary Schools - Trimurtini; Nugraheni, Nursiwi; Sari, Elok Fariha; Hamdani, Abtadi Tris; Khulafa, Faris Nur (An Overview of Literature, Language and Education Research Vol. 9, 2025)
Differentiated learning practices include adjusting the learning process, learning material content, learning outcome products, and learning environment with students' abilities. Geometry is a material element in mathematics with a large proportion of material in elementary school. Elementary school students face challenges in understanding abstract geometric concepts and potential interventions in their technology-based learning. The existence of technology is a necessity in learning geometry, but the readiness of students and facilities is still an obstacle faced in several elementary schools in Semarang. The purpose of this study is to identify and analyze the needs of elementary schools for the application of technology in differentiated learning on geometry materials. The research method used is quantitative descriptive. The research subjects were 47 people consisting of 41 4th-grade elementary school teachers and 6 elementary school principals in Semarang City. They filled out a questionnaire consisting of 14 questions about the urgency of differentiated learning applications in mathematics lessons, mainly on geometry materials. The results showed that 95.74% of the technology applications were needed in elementary schools, 87.77% were needed to differentiate learning on geometry materials, 78.72% were known to have a scope of ability in geometry including recognition, descriptive, and informal reasoning, 87.23% of problem-solving skills and spatial skills are needed in elementary school. The conclusion is that differentiated learning is an important strategy in basic education that aims to meet the diverse needs of students. The application of technology in differentiated learning in geometry material focuses on differences in initial abilities in the form of differences in the level of geometric thinking recognition and descriptive. This study's results can affect teachers' role in selecting appropriate technology applications for geometry learning.